Lean product engineering in the South African automotive industry. Issue 5 (1st June 2015) - Mund, Klaudia; Pieterse, Koot; Cameron, Sheila
Abstract : Purpose: – The puropse of this paper is to explore the extent to which principles of lean product development are applied to product design and engineering at automotive companies in South Africa (SA). Survey, interview and observational data form the basis for an adaptation of Toyota's lean product development system (LPDS) (Morgan and Liker, 2006) to the South African automotive product engineering context. Design/methodology/approach: – All seven automotive manufacturers then operating in SA (including Toyota) were investigated, together with sample of those suppliers carrying out product engineering and/or design locally. A questionnaire based on the LPDS, and follow-up interviews were used to ascertain the extent to which lean principles informed product engineering, and identify areas where there was scope for improvement. Findings: – The survey established that while SA automotive companies have a strong manufacturing focus there is very limited local product design and development (PD&D), as this tends to be carried out centrally for multinationals. However, global product designs require modifications to suit local conditions and many decisions about manufacturability are taken locally. This broad area of design-related activity will be termed product engineering. The study found considerable scope for increasing the extent to which aspects of product engineering were influenced by lean thinking. An adapted version of the LPDS is proposed to aid lean thinking in product engineering in this context. Originality/value: – This study provides information on the application of lean thinking in product engineering, an area that has attracted far less attention than manufacturing and PD&D. Furthermore it addresses a significant sector of an important emerging economy, and contributes a practitioner perspective to what is predominantly a theoretical literature.